Differences in Ratio in Formulas on The Performance of Local Male Rabbits - Kurniawan, Duwi; Yakin, Engkus Ainul (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Local rabbits are livestock with potential for development as a source of animal protein due to their high reproductive capacity, relatively rapid growth, and good adaptability to tropical environments. The success of rabbit farming is heavily influenced by the quality and quantity of feed provided; feed that fails to meet energy and protein requirements can lead to poor growth and reduced productivity. Therefore, proper ration formulation is essential to supply nutrients according to the animals' needs. This study aimed to determine the differential effects of ration formulas on the performance of male local rabbits, specifically regarding feed intake, average daily gain (ADG), and feed conversion ratio (FCR). The study was conducted over 28 days in Segawe Village, Jenawi District, Karanganyar Regency, using a Completely Randomized Design (CRD) with three treatments—P1 (40% forage + 60% concentrate), P2 (60% + 40%), and P3 (80% + 20%)—and four replicates. ANOVA and DMRT were used to evaluate the data. The findings demonstrated that while the ration formula had no significant influence (P>0.05) on ADG or FCR, it had a highly significant effect (P<0.01) on feed intake. Although P1 tended to be more physiologically efficient, P3 had the highest feed intake (156.65 g/head/day) and P1 had the lowest (117.37 g/head/day).